Association of Environmental Factors with Seasonal Intensity of Erysipelothrix rhusiopathiae Seropositivity among Arctic Caribou - O. Alejandro Aleuy; Michele Anholt; Karin Orsel; Fabien Mavrot; Catherine A. Gagnon; Kimberlee Beckmen; Steeve D. Côté; Christine Cuyler; Andrew Dobson; Brett Elkin; Lisa-Marie Leclerc; Joëlle Taillon; et al. (Emerging Infectious Diseases, 2022)
Several caribou (Rangifer tarandus) populations have been declining concurrently with increases in infectious diseases in the Arctic. Erysipelothrix rhusiopathiae, a zoonotic bacterium, was first described in 2015 as a notable cause of illness and death among several Arctic wildlife species. We investigated epidemiologic and environmental factors associated with the seroprevalence of E. rhusiopathiae in the Arctic and found that seropositivity was highest during warmer months, peaking in September, and was highest among adult males. Summer seroprevalence increases tracked with the oestrid index from the previous year, icing and snowing events, and precipitation from the same year but decreased with growing degree days in the same year. Seroprevalence of E. rhusiopathiae varied more during the later years of the study. Our findings provide key insights into the influence of environmental factors on disease prevalence that can be instrumental for anticipating and mitigating diseases associated with climate change among Arctic wildlife and human populations.